Application of Quick Response Code in Sea Turtle Conservation: Overcoming Limitations of Existing Individual Markers - Xia, Zhongrong; Yu, Haoqi; Yang, Fan; Liu, Xiaofeng; Yu, Dongmei; Hu, Huijian (Frontiers in Marine Science, 2022)
Hatchery release has been used for the conservation of green turtles for many years. In order to improve the rescue management of released individuals and avoid their negative impact on wild populations, the application of individual markers is particularly important. QR code was used to tag the individual of released turtles in Huidong Sea Turtle National Nature Reserve, the unique spawning site and nature reserve for sea turtles in China. The viscosity differences of four safe and non-toxic glues (epoxy resin, acrylic glue, ABS glue and nail gel 401) in different age groups were tested. The results revealed that epoxy resin glue has the best adhesion effect on eight-years-old turtles, and the intact rate after 50 days was 100%. It is suitable to be used for rescue of stranded turtle within 50 days of release. Nail gel 401 has the best adhesion effect on the carapace of one-year-old turtles with intact rate of 100% after 50 days, which can be used for short-time conservation of young turtle. The release experiments of 18 eight-year-old sea turtles with PIT, QR codes and steel tags showed that QR codes are conducive to public participation and improve rescue efficiency. In fact, QR code is a powerful measure to overcome the limitations of the existing individual label. However, the QR code fused with turtle carapace can only be applied for turtle rescue and tracing in a short-term due to its limited persistence.